CHALLENGES AND OPPORTUNITIES IN IMPLEMENTING FLIPPED CLASSROOMS IN EFL SETTINGS: A REVIEW OF CURRENT LITERATURE - Ameen O Saleh Almanafi; Siti Zuraidah Md Osman; Rabha Hassan Hamad Alghtani; Abdullahi Abubakar Yunusa (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This review examines the challenges and opportunities associated with implementing flipped classrooms in English as a Foreign Language (EFL) settings, drawing on recent literature to provide a comprehensive overview of current practices and findings. The flipped classroom model, which reverses traditional teaching methods by delivering instructional content outside the classroom and engaging students in active learning during class time, presents unique advantages for EFL learners, including increased engagement, personalized learning, and enhanced language proficiency. However, the implementation of this model is not without its challenges. Issues such as digital literacy, access to technology, and the need for effective instructional design can hinder successful adoption. Additionally, educators may face resistance to change from both students and institutional frameworks. This review highlights the importance of addressing these challenges through targeted professional development, the integration of appropriate technologies, and the establishment of supportive learning environments. Furthermore, it identifies opportunities for future research, including the exploration of best practices for flipped classroom implementation and the impact of various social media platforms on language learning outcomes. By synthesizing current literature, this review aims to provide insights for educators and researchers seeking to enhance EFL instruction through innovative pedagogical